ANALISIS STRATEGI KOMUNIKASI PEMASARAN PT RODA PEMBANGUNAN JAYA DALAM MEMASARKAN PERUMAHAN TAMAN PALAGAN ASRI DI YOGYAKARTA - Maharani, Bayu Krisna; Lestari, Puji; Basuki, Basuki (Jurnal Ilmu Komunikasi, 2009)
Developing business for real-estate is a very big business for future because this is about aspect of most people need in live. This reality inspired me to make a further research about real estate developer. The matters that this research about to raise is how PT. Roda Pembangunan Jaya attempt their strategic of marketing communications to achieve their company goal in selling unit of their real estate. The goal of this research is to knowing strategic of segmenting, targeting, positioning and form of the marketing style of PT. Roda Pembangunan Jaya in order to sell their unit in Taman Palagan Asri Real Estate. This research using method of qualitative description which is the researcher is trying to explained strategic of marketing communications of PT. Roda Pembangunan Jaya in case of selling Taman Palagan Asri Real Estate. The writer collecting data by doing an interview with the Marketing Manager of PT. Roda Pembangunan Jaya and according to PT. Roda Pembangunan Jaya record file. The analyze technique theory is using theory from Miles and Huberman which is about some essay and descriptive explanation. From the result of research we can know that PT. Roda Pembangunan Jaya taking seg- ment of consumer target from middle to high level of class according to housing positioning of Taman Palagan Asri Real Estate, that is housing for middle to high level class. The implementa- tion of positioning strategic to housing of Taman Palagan Asri conduct with three approaching such as positioning according to attribute, price and competitor. Advertising, personal selling and sales promotion is using to promote where advertising through billboard media is the most effective form of marketing communication. But there is some barriers to be face when implement marketing communication such as circumstances of global economic that not conducive but overall marketing communication that had been done running well.